시각언어 형태론 체계의 회화 창작 적용에 관한 연구 -‘母語詩-生愛慾死天’을 중심으로 - 장경기 (기초조형학연구, 2024)
본 연구는 디지털 기술과 인공지능(AI)의 발전이 시각적 이미지 창작에 제시하는 새로운 가능성을 배경으로, 시각언어의 형태론 체계를 회화 창작에 적용하는 방법을 탐구하였다. 연구는 구조주의 언어학에서 출발한 페르디낭 드 소쉬르의 기호학적 분석을 바탕으로, 언어의 기표와 기의, 계열체와 통합체의 개념을 시각적 창작에 적용하는 과정을 실증적으로 제시하고자 하였다. 특히, 2000년 전후의 디지털 시대 시문학 운동인 ‘멀티포엠아트’에서 차용한 ‘母語(모어, Mother language)’ 개념을 바탕으로,시각적 형태소의 생성과 통합을 통해 새로운 형태론적 회화 창작 방법을 제안하였다. 연구의 첫 단계에서는 내면의식을 탐구하여 시각적 기호인 ‘母語’를 생성하고, 이를 작품의 기본단위로 삼아 창작 과정을 진행하였다. 또한, ‘生愛慾死天’이라는 주제를 기반으로 ‘母語’들을 계열화하고 통합하여 ‘母語어휘구조’를 형성한 후, 디지털 기술을 활용해 시각적 문장 구조로 발전시켰다. 이러한 방식은 추상적 개념을 시각적으로 구체화하는 데 있어 창작자의 내면의식을 구조적으로 표현하는 방법을 제시하였으며, 롤랑 바르트의 기표연쇄, 로버트 R. 혼의 시각언어론, 자크 라캉의 기호학적 정신분석 이론을 적용하여 분석하였다. 결과적으로, 본 연구는 디지털 기술과 AI 기반의 시각적 창작 과정에서 시각언어의형태론적 체계가 회화 창작에 어떻게 적용될 수 있는지를 실증적으로 보여주었으며, 이를 통해 다언어적 시대의 예술 창작 방법론에 대한 새로운 가능성을 제시하였다. 이 연구는 또한 시각적 형태소의 변형과 결합을 통해 창작자가 내면적 경험을 시각적으로 체계화할 수 있는 방안을 제공하며, 회화뿐만아니라 다양한 디지털 매체에서의 창작 응용 가능성을 열어주었다. This study explores the application of the morphological system of visual language to paintingcreation, against the backdrop of new possibilities presented by the advancements in digitaltechnology and Artificial Intelligence (AI) in visual image creation. Based on Ferdinand deSaussure’s semiotic analysis, rooted in structural linguistics, the research empirically applies theconcepts of signifier and signified, syntagmatic and paradigmatic structures, to visual creation. Particularly, the study adopts the concept of ‘Mother Language,’ derived from the literarymovement of ‘Multi-Poem Art’ around the 2000s in the digital era, to propose a newmorphological method of painting creation through the generation and integration of visualmorphemes. In the initial phase, the study explores inner consciousness to generate visualsymbols called ‘Mother Language’ as the basic units of the artwork, and proceeds with thecreative process. Furthermore, based on the theme of 'Birth, Love, Desire, Death, and Heaven,’ itsequences and integrates ‘Mother Language’ symbols to form a ‘Mother Language LexicalStructure,’ then evolves this into a visual syntactic structure using digital technology. Thisapproach offers a method to structurally express abstract concepts visually, reflecting thecreator’s inner consciousness. The study analyzes these processes through Roland Barthes’theory of chain of signifiers, Robert E. Horn’s theory of visual language, and Jacques Lacan’ssemiotic psychoanalysis. Consequently, this study empirically demonstrates how themorphological system of visual language can be applied to painting creation in the context ofdigital technology and AI-based visual creation, proposing new possibilities for multi-linguisticart creation methods. Additionally, it offers ways for creators to systematically visualize innerexperiences through the transformation and combination of visual morphemes, extending itsapplications beyond painting to various digital media. KCI Citation Count: 0